Potensi Ekstrak Nabati dengan Pelarut Aceton dan Kloroform dalam Menekan Penyakit Busuk Batang oleh Jamur Sclerotium rolfsii Sacc. pada Tanaman Kacang Tanah - Mulat Isnaini (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2021)
The aim of the study was to evaluate potential of botanical leafs extracted with acetone and chloroform against fungal pathogen Sclerotium rolfsii causing basal stem rot on peanut. In-vitro tests involved 6% aceton and or chloroform (0,3 mL) were added into each leaf extracts it then pour into agar medium 100 mL. Four leaf extracts used “ Sirih Hijau (SH); Sirih Merah (SM); Babandotan with aceton (Bb) dan Patikan Kebo (PK). The study was disgned by Completely Randomized Design with ten replicates per treatment. Bioassay test was conducted in the glasshouse involved soaking seeds in leaf extracts i.e: ASH, KSH and ABb for 30 min and as control treatment, seeds were soaked in sterile distiled water. Seeds were planted in soil mixed in the plastic bag with 5 seeds per bag. Those bags were arranged in the glass house with Completely Randomized Design with 7 replicats per treatment . Fungal S. rolfsii pathogen was inoculated when plants reached two paiars of the leaf. The results showed that “Sirih hijau extracted with aceton (ASH) and Sirih merah extracted with chloroform (KSH) and Babandotan extracted with aceton (ABb) were effectif inhibiting mycelial growth of S. rolfsii in medium agar (100%). In the glasshouse study treatement of “ASH was the most effective in controlling disease incidence (51,43 %) compared with two other treatments, “KSH and Abb” were about 20 %.